Assessment of scatter radiation in the shielding of radiography procedures - Duarte, Maria (2022)
Scattered radiation is the largest contributor to patient dose and the main cause for stochastic effects (1-3). Evaluate the use of radiological protections and attenuating materials depending on the scattered radiation which the patient is subject, analyzing the appropriate placement of the protections is extremely important for the improvement of the radiographer clinical practice (4-7). Therefore, the purpose of this research is to ascertain the best way to protect irradiated patients, particularly children and pregnant women.